ANALISIS IMPLEMENTASI KURIKULUM IPS PADA JENJANG PENDIDIKAN DASAR - Abdul Manaf (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2018)
Talking about the concept of education cannot be separated from the curriculum. Because the competence of graduates has been decided, the necessary framework and scope of materials to be prepared to be learned and mastered by teachers as main actors of education as stated in Government Regulation No. 20, 2003 of the national education system, in chapter 19 verse one: that the curriculum is a set of plans and arrangements concerning the objectives, content, and materials and how are used as guidelines for learning activities to achieve specific educational goals. The concept of IPS education in this case is an idea that describes the relationship between two or more facts such as the concept of